Analyzing employer branding and its impact on talent acquisition with special reference to it sector - Sudhan sk, Indira singh, ajay kumar tyagi, nagendra pal singh, Shital deshmukh (Journal of Informatics Education and Research, 2025)
The it sector in india is perceiving unprecedented growth, escorted by intense competition to attract extremely skilled professionals. The deficiency of competent talent & the rising demand for expert digital skills have forced organizations to distinguish themselves through robust employer_branding. Employer_branding reflects how potential personnel perceive the firm as a place to work. It incorporates the company’s principles, ethics, work environment, compensation structure & overall reputation. Talent_ acquisition is no longer limited to filling vacancies; it includes building long-term relations, creating a robust employer value proposition & ensuring an engaging employee practice. In the it sector, where skilled experts have multiple opportunities, employer_branding serves as a strategic recruitment instrument that influences job seekers' decisions. In an increasingly competitive information technology (it) environment, organizations are purposefully focusing on